Evaluating Preschool Programs When Length of Exposure to the Program Varies: A Nonparametric Approach - Behrman, Jere R.; Cheng, Yingmei; Todd, Petra E. (The Review of Economics and Statistics, 2004)
Nonexperimental data are used to evaluate impacts of a Bolivian preschool program on cognitive, psychosocial, and anthropometric outcomes. Impacts are shown to be highly dependent on age and exposure duration. To minimize the effect of distributional assumptions, program impacts are estimated as nonparametric functions of age and duration. A generalized matching estimator is developed and used to control for nonrandom selectivity into the program and into exposure durations. Comparisons with three groups—children in the feeder area not in the program, children in the program for ≤ 1 month, and children living in similar areas without the program—indicate that estimates are robust for significant positive effects of the program on cognitive and psychosocial outcomes with ≥ 7 months' exposure, although the age patterns of effects differ slightly by comparison group.